Mediated boyhoods: boys, teens,and young man in popular media and culture - "Wannamaker, Annette .(ed.)" (New York, 2011)
Mediated Boyhoods: Boys, Teens, and Young Men in Popular Media and Culture brings together work from various disciplines that explores the relationships among the everyday lives of boys and such media platforms as television, films, games, sports, music, urban and suburban culture, fashion, young adult novels, Facebook, MySpace, and YouTube. Offering a comprehensive overview of boyhood studies, chapters consider questions about the current state of boyhood as it is represented in the popular media; the ways that boys are influenced by and work to influence popular culture; the ways that popular texts often reflect adult expectations, anxieties, and prejudices about boys and boyhood; and the ways that boys, teens, and young men are often able to reflect upon and to act, sometimes unpredictably, to resist, subvert, or re-imagine and re-create popular culture and media.
Keywords: Teenagers in mass media